ESTIMASI KARBON ABOVE GROUND JENIS SENGON DAN SERESAH DI HUTAN RAKYAT DESA BATEH KECAMATAN CANDIMULYO KABUPATEN MAGELANG - , IMAM MUJIONO; , Dr. Ir. Ris Hadi Purwanto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of factors that influence the content of biomass of forest stands is the structure of forest stand. Problems in information management activities on forest biomass potency of community forest is the high variation on forest conditions due to the complexity of cropping pattern and stand structure. The diversity of stand structure complicates the prediction process and dynamics modeling of forest biomass. Therefore, it is required a simplification strategy of stand structure variations on community forest to facilitate the handling stategy or future silviculture treatment to integrate community forest functions as timber and carbon producing. This study was conducted in community forests located in Desa Bateh, Kecamatan Kabupaten Magelang, Central Java. Sampling was conducted with a purposive method to land owned by ilustration of stand structure variation in research location. Grouping stand structure of community forest used the Kmeans cluster methode. Estimation of standing biomass amount used equations allometrik and litter biomass estimation conducted by litter weight dry measurements, while the amount of carbon is 40% - 50% of biomass component composition. The result shows that, there are three cluster of community forest stand structures have different character, so that the store of biomass content also different. The distinguishing characteristic of amount of stand carbon content is the density of stand basal area, stem diameter and biomass content of litter which is influenced by amount of vegetation in community forest.